Effect of sulfation and partial hydrolysis of polysaccharides from Polygonatum sibiricum on immune-enhancement - Khamphone Yelithao (2018)
© 2018 Elsevier B.V. The aqueous polysaccharide from Polygonatum sibiricum was extracted and fractionated using anion-exchange chromatography to obtain F1 fraction. The F1 was chemically sulfated and partially acid-hydrolyzed for the production of its over-sulfated (OS1,2,3) and hydrolyzed (HP1,2,3) derivatives, in which the sulfate content of OS1,2,3 was 7.5–17.1%, and the Mw of HP1,2,3 ranged from 18.2 × 103 to 57.3 × 103 g/mol. Considerable RAW264.7 cell activation was observed by HP1,2,3 with NO production of 34.9, 44.3 and 42.7 μM, respectively, as well as the mRNA expression of cytokines (IL-1β IL-6, IL-10 and IL-12). NK cell cytotoxicity against HT-29 cell was facilitated by OS1,2,3 treatment with the increased gene expressions of INF-γ Granzyme-B, perforin, NKG2D, and FasL. RAW264.7 cells appeared to be activated via MR and TLR4 mediated signaling pathway, but CR3 and TRL2 might play a main role in stimulating NK cells. Overall, the present study suggests the potential application of polysaccharides from P. sibiricum in functional foods and pharmacological industries.